Therapeutic effects of an innovative BS-HH-002 drug on pancreatic cancer cells via induction of complete MCL-1 degradation - A-min Wang (Elsevier, 2022)
BS-HH-002 is a newly developed drug with excellent antitumor activity, which resulted from the modification and optimization of the side structure of the homoharringtonine (HHT). It is particularly efficient in treatment for acute myeloid leukemia and myelodysplastic syndromes. Here we tested whether BS-HH-002 also had anti-cancer effects on solid tumors, especially pancreatic cancer. The results showed that BS-HH-002 treatment resulted in the complete degradation of the anti-apoptosis protein MCL-1, thereby inhibiting proliferation and inducing apoptosis of pancreatic cancer cells. In contrast, BCL-2 and BCL-XL protein levels were still detected in apoptotic cells. Further, we compared HHT and BS-HH-002 in terms of PK and heart toxicity in animals. Compared to HHT, BS-HH-002 quickly reached high blood concentration after intravenous injection or oral administration, without causing obvious cardiac toxicity. These results indicate that BS-HH-002 is a promising new anti-cancer drug to treat pancreatic and other solid tumors.